Effects of time-restricted feeding and walking exercise on the physical health of female college students with hidden obesity: a randomized trial - Liu, Haitao; Chen, Shiying; Ji, Haoyuan; Dai, Zuanqin (Frontiers in Public Health, 2023)
Purpose: Time-restricted feeding (TRF) is an emerging dietary pattern with many potential effects. This study focused on the effects of TRF and walking on the physical health of female college students with hidden obesity. Methods: A total of 77 female college students with hidden obesity, aged 18–22 years, were randomly assigned to a control group (CON, N=19), time-restricted feeding group (TRF, N=19), exercise group (EXE, N=20), and TRF combined with exercise group (TRF+EXE, N=19). The interventions lasted for 8 weeks. Tests assessing body shape, body composition, bone mineral density, blood lipid levels, and blood pressure were performed before and after the intervention. Results:(1) Intragroup comparison before and after the intervention revealed that the TRF, EXE, and TRF+EXE groups had significantly reduced body weight (P<0.01), body mass index (BMI) (P<0.05), and lean tissue mass (LTM) (P<0.01) but increased total cholesterol (TC) levels (P<0.05) after the intervention. Body fat percentage (BF%) increased considerably in the EXE and TRF+EXE groups (P<0.01). (2) Post-intervention comparisons of body weight, BMI, LTM, adipose tissue mass (ATM), total bone mineral density (TBMD), blood lipid levels, and blood pressure between the intervention groups (TRF, EXE, and TRF+EXE) and the CON group showed no significant differences (P>0.05). (3) A comparison of the changes between the groups before and after the intervention showed significant decreases in body weight in the TRF and TRF+EXE groups (P<0.05) and in both BMI and LTM in the TRF, EXE, and TRF+EXE groups (P<0.05) compared to those in the CON group. The BF% change in the EXE and TRF+EXE groups were significantly greater than that in the TRF group (P<0.01). Conclusions: TRF effectively decreased body weight and BMI in female college students with hidden obesity. However, increased blood lipid levels and decreased LTM levels were also observed. The effects of TRF combined with exercise were not superior to those of TRF or walking alone in terms of body weight, body mass index, body composition, TBMD, or blood lipid levels. Therefore, TRF cannot be considered the best option for fat reduction in female college students with hidden obesity.